Incertezza e cambiamento climatico nell’era dell’Antropocene - Elena Bougleux (EtnoAntropologia, 2017)
Climate change appears as a major driver of identity crisis, affecting changes at local and global level in terms of spaces, security, livelihood and weather. The prevailing narration on climate change describes unfamiliar scenarios struck by exceptional events, that rarely can be connected with personal experiences. Yet, smaller but more subtle consequences of climate change occur in cities and in metropolitan areas, that suddenly appear fragile and risky contexts. The paper explores the notion of climate change, which is investigated in its constructive dimensions considering how scientific facts and social meanings contribute to shape the very notion of climate, across time and across disciplines.